The Role of Tourism Education in the Promotion of Tourism. The Case of Greece in the Period 2005-2020 with Particular Reference to the Pandemic Era - Karioti, Vassiliki; Vathi-Sarava, Panagiota (Archives of Business Research, 2022)
Nowadays, tourism appears to be one of the most developing sciences to research and study. Over the last decades, the industry of travel and tourism has evolved significantly, increasing its pace of common development year by year. For the Greek Economy, tourism is a central pillar of development and growth with significant contribution to Gross Domestic Product increase, employment, and investment. The rich cultural heritage, extensive coastline and natural environment are some of the basic advantages that make the country one of the most important tourist destinations worldwide. Considering the impact tourism has on our country, we understand the role that tourism education can play in the shaping of tourism consciousness and, consequently, in promoting social and economic development. Thus, it is necessary to study some elements in order to reach conclusions that will help to improve our tourism consciousness. In this paper, we will deal with tourism data (referring to the period 2005-2020 https://insete.gr/bi/inbound-tourism-total-country) using statistical process control, specifically time series control charts. We use Box-Jenkins methodology to find models of time series in Annual Changes of Income from 2005-2020, of Arrivals from 2010-2020 and the Average per capital expenses from 2005-2020. Specifically, we test models’ sensitivity in detecting even small shifts in mean which may indicate financial instability. This analytical approach is widely applicable and therefore of theoretical and practical interest. Based on the results of this approach could propose the inclusion of introductory tourism education courses in all levels of education. The Greek tourism industry is thus expected to benefit from the financial and wider benefits of education.